Developing an Effective Sharia Bookstore Prototype using Waterfall Method - Fajar Andrean Syah; Tutik Khotimah; Hanik Hidayati (International Journal of Informatics and Computation, 2025)
Traditional Islamic bookstores, such as Toko Kitab Mu’asifa, rely on manual record-keeping, which is prone to errors, slow in reporting, and inefficient in inventory management. This study presents the results of Black Box testing conducted on a web-based digital library application developed using the Waterfall methodology. A total of seven critical features were evaluated, including administrator login, customer login, book management (add, update, delete), purchase transactions, and user management, with test scenarios designed to simulate real user interactions. The testing outcomes indicate that all features functioned according to the specified requirements, achieving a 100% success rate with no recorded errors or failures. These results demonstrate the robustness, reliability, and accuracy of the system in managing essential operations such as authentication, inventory handling, and transaction processing. The findings confirm that the application is functionally ready for deployment; however, further evaluations focusing on non-functional aspects such as performance, security, and scalability are recommended to ensure comprehensive system readiness in real-world usage. The integration of Sharia values positions this system not only as a business management tool but also as a model of Islamic information systems that can be adapted by similar enterprises.